ANALISIS KEPUASAN KONSUMEN TERHADAP PRODUK SEMBAKO PADA MINIMARKET JUAN DI KECAMATAN BENAI KABUPATEN KUANTAN SINGINGI - Mulyeni Fitri; Jamalludin Jamalludin; Chezy WM Vermila (Universitas Tribhuwana Tunggadewi, 2020)
The purpose of this study was to determine the behavior and consumer satisfaction of consumers of basic food products at the Juan minimarket in Benai District. The method used in this study is the Likert scale and analysis method (IPA) and (CSI) or Consumer Satisfaction Index. The results obtained from consumer behavior towards rice are in the satisfied category, with a total of 16 people from 30 respondents with a percentage of 53.33%, sugar and cooking oil in the category of Very Satisfied with 23 souls from 30 respondents with a percentage of 76.67% %, eggs are in the satisfied category with 25 souls from 30 respondents with a percentage of 83.43%, milk is in the very satisfied category with a total of 17 souls from 30 respondents with a percentage of 56.67%. And the results of the calculation of rice as a whole the value of the index of consumer satisfaction is 69.50%. Where this value is in the consumer satisfaction index range of 50% -75%. Sugar consumer satisfaction index value of 59.57% CSI results are in satisfied criteria, cooking oil consumer satisfaction index value is 72.00% and CSI results are on very satisfied criteria, egg consumer satisfaction index value is 76.00% based on CSI results are in the criteria of satisfaction and milk the consumer satisfaction index value is 70.00%.